Puja Mandala in Benoa, Badung, Bali as the Model of Religious Tolerance - Muhamad Fajar Pramono*; Farissa Azmia Hud (Journal of Comparative Study of Religions, 2021)
This research discusses the model of religious tolerance in Puja Mandala,Benoa, South of Kuta, Badung, Bali. Puja Mandala is an area with Mosque, CatholicChurch, Monastery, Christian Church, and Temple stand side by side. This researchalso discusses the supporting factors of religious tolerance in Puja Mandala, how dothey can communicate well and keep the harmony until now. Generally, Bali societyhas been dependent on upright religious tolerance far away before Puja Mandalawas built. This is supported by Hindu Teaching, Tri Hita Karana to do and get intouch well with other humans without seeing their religions, ethnicities, or eventheir tribes. The Research data had been taken from interview results with somereligions’ leader and some officials from each house of worship in Puja Mandalawith a qualitative method. Besides, the researcher also has observed and takensome documents from each house of worship as an accurate additional reference